Climate and human activities alter coupling of soil macro- and micronutrients: Evidence from a long-term experiment in typical steppes - Yi Zhou; Shenghua Chang; Xiaojuan Huang; Wenjun Wang; Fujiang Hou; Yanrong Wang; Zhibiao Nan (Geoderma)
Soil nutrients are essential for ecosystem function and food production. However, the long-term dynamics and ecological drivers of soil macro- and microelements, as well as their relationships, remain virtually unknown, especially in varying precipitation contexts. Here, we conducted a long-term experiment in typical steppes to explore the universal and differential mechanisms of soil macro- and microelements along the precipitation gradient. Our results showed decreases in soil Zn and Fe stocks, alongside increases in Cu, SOC, and STN stocks over time. From north to south, the temporal stability of SOC, STN, Cu and Zn stocks generally increased. Additionally, compared to the humid site, soil macronutrients showed stronger coupling with micronutrients at the arid site, especially Fe, followed by Mn, Zn, Cu. The sensitivity of soil macro- and microelements to climate change and human activities were correlated with the local background precipitation. Precipitation fluctuation, GDP per capita and current precipitation were significant factors contributing to the variation in soil macro- and microelements stock in the north, center and south. Climate explained 46%, 19%, and 16% of nutrient coupling variation in the north, center, and south sites, respectively. Across all sites, human activities explained 74% of variation. Altogether, our findings provide an overview of long-term soil macro- and microelement distribution, their coupling relationships, and driving factors under different precipitation contexts, which is important for grassland management and food production in future global change scenarios.